(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The hereafter text is extracted from Elizabeth Grosz’s book Chaos, Territory, Art: Deleuze and the Framing of the Earth (2008). In it, Grosz focuses on the conditions of art’s existence as a separation and ordering of compositional planes within chaos imanente on the natural world. Her explorations are guided by the writings of Gilles Deleuze, Félix Guattari, and Luce Irigaray, who propose openings of nature and culture to unrecognized and undetermined forces, emerging from the natural chaos. Grosz understands that such forces can promulgate new ways of conceptualizing politics and the ways in which art and politics can be connected and rethought.